Youth and community empowerment in Europe : [international perspectives] - Evans, Peter, 1924-; Kruger, Angelika (Bristol : Policy, 2012)
This book provides the theoretical context for the Youth Empowerment Partnership Programme programme. It gives a full account of the process and outcomes of its unique development and reflects on the lessons learnt for future policy.
Title from publisher's bibliographic system (viewed on 07 Sep 2022).
Keywords: Community power -- Europe; Youth with social disabilities -- Services for -- Europe